PELAKSANAAN FUNGSI PEMERINTAH DESA DALAM PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM TENUN IKAT (STUDI DESA GAYAK, DESA HARUBALA DAN DESA NOBO KECAMATAN ILEBOLENG KABUPATEN FLORES TIMUR) - Selviana Barek Boro; Rafael Rape Tupen; Hernimus Ratu Udju (Petitum Law Journal, 2026)
This study examines the role of village government in empowering communities through the ikat weaving program in Harubala, Gayak, and Nobo Villages (East Flores). Findings indicate a mismatch in policy implementation: Gayak and Nobo Villages provide budget support and form groups, despite not having specific Village Regulations, while Harubala does not make this program a priority in the RPJMDes/RKPDes. Several major inhibiting factors include: (1) The quality of human resources in village officials (most of whom have a high school education) who are inadequate in formulating policies, understanding regulations (e.g. HAKI), and providing support; (2) Marketing constraints (depending on the local market, lack of use of digital technology, and competition between villages); and (3) Inadequate infrastructure (no weaving houses and limited production tools). The impact of empowerment was only felt significantly in Gayak with an increase in women's income, while the program in Harubala and Nobo stagnated or stopped. To optimize the role of the village government, there needs to be strengthening of subsidiarity-based policies, increasing human resource capacity, providing strategic facilities, and integrating modern marketing so that cultural potential can be transformed into a sustainable economic basis.